2020
DOI: 10.29240/ef.v4i2.1494
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning amidst Global Pandemic: EFL Students’ Challenges, Suggestions, and Needed Materials

Abstract: Covid-19 pandemic brings changes in many aspects of peoples’ lives throughout the world. The spread of Covid-19 in Indonesia affects the education system in this country. Face-to-face instructions are shifted into full online learnings from home. Despite this quite drastic change, the literature on students’ insights of this matter has still been silent. Thus, the present study elucidates 45 EFL students’ challenges, suggestions and needed materials during these online classes. Rely on qualitative data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 24 publications
10
99
1
4
Order By: Relevance
“…Unfortunately, the connection was sometimes unstable, and it consumed a lot of internet quota. This contrasts with a study done by (Nartiningrum & Nugroho, 2020), who mentioned the students' suggestion to use Zoom and Google Meet as a solution for the absence of student-teachers interaction. Besides, Kahoot was unfamiliar to both lecturers and students.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Unfortunately, the connection was sometimes unstable, and it consumed a lot of internet quota. This contrasts with a study done by (Nartiningrum & Nugroho, 2020), who mentioned the students' suggestion to use Zoom and Google Meet as a solution for the absence of student-teachers interaction. Besides, Kahoot was unfamiliar to both lecturers and students.…”
Section: Discussioncontrasting
confidence: 63%
“…The interpreted data revealed that lecturers provided more than four online applications. It was contrary to the fact that the Head of the English Education Program had instructed all lecturers to provide one or two familiar and economical online learning applications since most students complained about the internet's problems such as the excess of quota and unstable internet access (Nartiningrum & Nugroho, 2020). Besides, a few of them were unfamiliar to operate online learning applications at the beginning of online learning.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Emergency online teaching of English also involves certain constraints, as the findings show. The sudden and unplanned transition to emergency remote teaching left all parties in education, including language teachers, students and their families, in a challenging situation (Hadianti & Arisandi, 2020) since online teaching necessitated access to a stable internet connection, an effective online platform or learning management system and access to smartphones, computers and desks that were reported to be lacking, hindering the effectiveness and efficiency of English language teaching during the pandemic (Almekhlafy, 2020;Atmojo & Nugroho, 2020;Huang et al, 2021;Nartiningrum & Nugroho, 2020;Novikov, 2020;Rahman, 2020;Shahzad et al, 2020;Turchi et al, 2020). Apart from these, teachers and learners having insufficient knowledge about online teaching and learning, teachers' lack of control over online teaching platforms, and making use of less varied and engaging teaching activities or lack of direct interaction during the courses were among the most reported weaknesses of online teaching during the pandemic (Bailey & Lee, 2020;Huang et al, 2021;Nartiningrum & Nugroho, 2020;Sepulveda-Escobar & Morrison, 2020;Shaaban, 2020).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 99%
“…Regarding English language teaching and learning through emergency online teaching, several research studies were conducted dealing with various aspects involving teachers, students, teaching practices, technological resources, teaching platforms, and the teaching of language skills from primary to university education (see, for example, Andriivna et al, 2020;Jones, 2020;Maican & Cocoradă, 2021;Nartiningrum & Nugroho, 2020;Russell, 2020;Sepulveda-Escobar & Morrison, 2020). In fact, not only for the existing situation of English language teaching during emergency online teaching but also for the occurrence of a crisis in the future necessitating a sudden shift to emergency teaching, the evidence and experience gathered from research studies may provide valuable insights into the nature of English language teaching in such periods.…”
Section: Introductionmentioning
confidence: 99%